Pengaruh DPK, CAR, dan FDR Terhadap Pembiayaan Murabahah dengan ROA Sebagai Variabel Moderating - Pratiwi, Yunita Indah; Nabila, Rifda (IAIN Kudus, 2022)
This study aims to determine the effect of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR) on Murabahah Financing with Return On Assets (ROA) as a moderating variable. The population in this study is all Islamic Commercial Banks in Indonesia that publish their quarterly financial reports at the Otoritas Jasa Keuangan (OJK) and also on the official website of each Islamic Commercial Bank for the period 2016 to 2020. The sampling technique uses purposive sampling technique. and get a sample of 10 Islamic banks. And analyzed using the technique of moderated regression analysis (MRA). The results in this study are: (1) DPK has a positive and significant effect on murabahah financing. (2) CAR has no effect on murabaha financing. (3) FDR has no effect on murabaha financing. (4) ROA cannot moderate the effect of DPK on Murabahah Financing (5) ROA cannot moderate the effect of CAR on Murabahah Financing (6) ROA cannot moderate the effect of FDR on Murabahah Financing. The implications of the results of this study can be used by Islamic bank management in an effort to control the amount of financing to be distributed by taking into account the amount of Third Party Funds (DPK) obtained by Islamic banks.